Carbon balance and greenhouse gas emissions from horticultural plants grown in peat-based growing media - Sharma, Bidhya; Moore, Tim R.; Roulet, Nigel T. (Frontiers in Horticulture, 2025)
Peat-based growing substrates are commonly used in specialty crop production. The decomposition rates of peat and the respiration dynamics of plants grown in peat mixtures are poorly understood. We grew lettuce (Lactuca sativa) and petunia (Petunia sp.), representing food and ornamental plant growth, in peat-based media and measured the exchange of carbon dioxide (CO2), nitrous oxide (N2O), and methane (CH4) over 3 to 4 months. We used radiocarbon isotopes to partition ecosystem respiration (ER) into autotrophic respiration (AR) and heterotrophic respiration (HR) and estimated the priming effect of roots to enhance peat HR. Average (± standard deviation) N2O emissions were 2.69 ± 3.47 mg m−2 day−1, while CH4 emissions were variable and small. HR measured from peat alone was on average 0.28 ± 0.15 g CO2-C m−2 day−1. Average net ecosystem exchange (NEE) and ER measurements for pots containing lettuce were −1.17 and 2.09 g CO2-C m−2 day−1, respectively, and NEE and ER for pots containing petunia were −0.62 and 2.96 g CO2-C m−2 day−1, respectively. Without considering the priming effect, HR contributed 9% and 13% to the total ER in lettuce and petunia, respectively. Radiocarbon partitioning of ER revealed that HR contributes 10% and 18% for lettuce and petunia, showing a statistically significant positive priming (p = 0.007) effect in petunia but not in lettuce. Our measurements provide a basis for the reporting of GHG emissions from horticultural plants grown in peat-based growing media.